ANALISIS PELAKSANAAN STRATEGI PENJUALAN PRODUK OLAHAN LIDAH BUAYA PADA PD TRIPLE PONTIANAK - Horiyeh Horiyeh; Bambang Genjik S; Warneri Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis research originated from the problem “Implementation of Sales Strategy forProcessed Aloe Vera Products at PD. Triple Pontianak”. The sub-problems in thisstudy are (1) achieve sales volume of processed aloe vera products in PD. Triple?, (2)get profit from aloe vera productsin PD. Triple?, and (3) support the growth ofprocessed aloe vera product companies in PD. Triple?. The aim of this study is todetermine the implementation of the sales strategy of processed aloe vera products atPD.Triple Pontianak. The method used in this research is descriptive method andcolleting data using survey. Sources of the data in this research are the owne,secretary and treasurer. Data were collected using some instruments such asinterview, observation, and others supporting documents. Based on the results ofinterwiew and observation, it is shown that the implementation of the sales strategy foraloe vera products in PD.Triple Pontianak is quite good. This can be seen from theabillty of the company owner to carry out the sales strategy of processed aloe veraproducts, so that members feel satisfied with the owner in planning targets and effortsto increase sales volume based to the planned target.Keywords: implementation, sales strategy, product.